Optimization of the Police Goes to School Program to Prevent Traffic Violations in the Order of Maintaining the Bogor Police Satlantas Dikyasa Unit - Akhsani Taqwim, Muhammad Daffa (Police Studies Review, 2024)
This research is motivated by the high number of violations and traffic accidents involving millennial generation or students that occur in the Bogor Police jurisdiction. This can happen because there are several indications of problems, including the lack of knowledge of adolescents about traffic and road rules, the existence of indifferent attitudes towards the appeal of the police, and the existence of a pattern of undisciplined behavior in traffic. Dikmas Lantas has a program aimed directly at raising awareness of traffic discipline through the Police Goes To School program, especially to high school students in the Bogor Regency area. As a knife analysis of the problems in this thesis, the authors use the basic management functions proposed by George R. Terry covering Planning, Organizing, Actuating, and Controlling as well as the six elements of "M" management consisting of Man, Materials, Machines, Methods, Money and Markets. In addition, the author uses communication theory by Harold D. Lasswell who explains the question Who Says What In Which Channel To Whom With What Effect ?. This study uses a qualitative approach and type of research field research to obtain information and data needed as well as data collection techniques used are observation, interviews and document studies. The results of research conducted by the author on the implementation of the Police Goes To School program in order to prevent traffic violations are in accordance with the SOP of Police Goes To Campus and School, but in its implementation there are several problems such as no planned daily, weekly, or monthly activities. In addition, there are internal and external factors that hamper the implementation of activities and the lack of ability of members to communicate. Therefore, the authors provide advice to empower students as ambassadors of orderly traffic, make games through websites, and improve the ability of personnel in communication so that the program can create kamseltibcar then.